EXISTENTIALISM FEMINISM REFLECTED IN ACEVEDO’S WITH THE FIRE ON HIGH: Existentialist Feminism, Domestication of Women, Transcendence - Berya Kamayan Adi Martinus (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2022)
Women are frequently treated as second-class in patriarchal societies, which it eventually leads to feminist movements. There are various schools of feminism, such as liberal feminism, Marxist and socialist feminism, existentialist feminism, radical feminism, and so on. The focus of this study is on existentialist feminism exposed in Elizabeth Acevedo's With the Fire on High (2019). This study examines the domestication of women depicted in Emoni Santiago’s character and Emoni Santiago’s ways embrace her conditions and existing as a woman in the novel. To analyse Emoni’s appearance as a real woman who can exist, Simone de Beauvoir's existentialist feminism is applied. This study is a descriptive qualitative research that applies a feminist approach. The result shows that the domestication of women reflects in pregnancy, mothering, and cooking activity of Emoni Santiago. She can work in domestic and public spheres as her efforts to embrace women’s destiny, history, and myth. She also becomes an intellectual woman who is good at cooking because she is talented and creative. She also can play a significant role in the Culinary Arts program and become the transformative agent that can persuade her community that women can exist without being limited by women's conditions. She reflects existentialist feminism because she can do tasks in domestic and public spheres. She manages to become a woman who is not dependent and subordinate to men in terms of economics, life choices, and marriage. All how Emoni Santiago's existence can appear are called the transcendence of women in today's life. According to Simone de Beauvoir, women's lives today can transcend all boundaries by doing a state of transcendence. Women can go beyond being equal to men through 4 tactics - women can work, become intellectuals, and play roles that make them transformative agents and independent. By achieving a state of transcendence, Emoni can eradicate woman labels such as second sex, the Other, and the weaker. From the result of the analysis, the writer finds out that women can exist as real women by doing transcendence.